chapter4-sol-HW

chapter4-sol-HW - Chapter 4 Single Degree-of-Freedom...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Chapter 4 Single Degree-of-Freedom Vibration: General Loading and Advanced Topics Problems for Section 4.1 &Arbitrary Loading: Laplace Transform 1. Solve the following equations of motion using the Laplace transform approach: (a) & y + 2 _ y + 3 y = 5cos3 t; y (0) = 3 ; _ y (0) = 4 (b) 4& y + 5 _ y + 5 y = 4 u ( t ) ; y (0) = 1 ; _ y (0) = 1 , where u ( t ) is the unit step function, (c) 3& y + 3 _ y + 6 y = 3 e & t + 2cos3 t; y (0) = 2 ; _ y (0) = 4 (d) & y + _ y + y = F ( t ) ; y (0) = 0 ; _ y (0) = 0 , where F ( t ) is given by a square wave function with maximum amplitude 1 and period 1, (e) & y + 2 _ y + 3 y = cos3 t + cos5 t; y (0) = 0 ; _ y (0) = 0 . Solution: The Laplace transform of the general equation m & y + c _ y + ky = F ( t ) is m & s 2 Y ( s ) & sy (0) & _ y (0) + c ( sY ( s ) & y (0)) + kY ( s ) = F ( s ) ; where y (0) and _ y (0) are the initial conditions, and where Y ( s ) and F ( s ) are the Laplace transforms of y ( t ) and F ( t ) ; respectively. Then, Y ( s ) = F ( s ) + m ( sy (0) + _ y (0)) + cy (0) ms 2 + cs + k : The inverse Laplace transform of Y ( s ) gives y ( t ) : Let us now do the individual problems. (a) & y + 2 _ y + 3 y = 5 cos 3 t , y (0) = 3 , y (0) = 4 In this case, m = 1 ; c = 2 ; k = 3 ; and F ( s ) = 5 s= ( s 2 + 9) where F ( s ) is obtained from the Laplace transform table (Table A.2). The Laplace transform of the response, Y ( s ) ; is given by Y ( s ) = ( 5 s s 2 +9 ) + 3 s + 10 s 2 + 2 s + 3 = 3 s 3 + 10 s 2 + 32 s + 90 ( s 2 + 9)( s 2 + 2 s + 3) : The inverse transform can be found using a symbolic program. Alternatively, to perform the inversion by hand, we need to rewrite Y ( s ) using the method of partial fraction expansion. Y ( s ) can be rewritten as 3 s 3 + 10 s 2 + 32 s + 90 ( s 2 + 9)( s 2 + 2 s + 3) As + B ( s 2 + 9) + Cs + D ( s 2 + 2 s + 3) ; 1 2 CHAPTER 4 SDOF VIBRATION: GENERAL LOADING where the assumed numerators depend on highest order of the numerator of the original fraction. Equating, we &nd that 3 s 3 + 10 s 2 + 32 s + 90 = ( As + B ) & s 2 + 2 s + 3 + ( Cs + D ) & s 2 + 9 = ( A + C ) s 3 + ( B + D + 2 A ) s 2 + (3 A + 2 B + 9 C ) s + 3 B + 9 D: Matching coe cients, we obtain A = & 5 = 12 ; B = 5 = 4 ; C = 41 = 12 ; D = 115 = 12 : Then, Y ( s ) = & 5 s= 12 + 5 = 4 ( s 2 + 9) + 41 s + 115 12( s 2 + 2 s + 3) : To transform Y ( s ) to y ( t ) ; &rst we must rewrite Y ( s ) in the following form, Y ( s ) = & 5 12 s ( s 2 + 9) + 5 12 3 ( s 2 + 9) + 41 12 s + 1 ( s + 1) 2 + & p 2 2 + 74 12 1 p 2 p 2 ( s + 1) 2 + & p 2 2 : The inverse transform is then given by y ( t ) = L & 1 [ Y ( s )] = & 5 12 cos3 t + 5 12 sin3 t + 41 12 e & t cos p 2 t + 37 p 2 12 e & t sin p 2 t = & : 417cos3 t + 0 : 417sin3 t + exp( & t )(3 : 42cos1 : 41 t + 4 : 36sin1 : 41 t ) : The response plot is shown at the end....
View Full Document

Page1 / 8

chapter4-sol-HW - Chapter 4 Single Degree-of-Freedom...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online